PTIMALISASI PERANAN BPK DALAM PENGAWASAN KEUANGAN NEGARA SECARA TRANSPARAN DAN AKTUAL - Bambang Triadji (Media Riset Akuntansi, Auditing & Informasi, 2003)
Reform era demands a clean state administration that frees from corruption, collusion, and nepotism. As such, BPK-RI, which is established on UUD 1945 has its ow function in auditing the accountability of the state financial management, has to optimize its role in more transparent and actual manner.In its implementation, BPK-Rl faces many obstacles such as limited authority as regulated in several acts, interdeparfment relationship, working standards, and the overlapping among audit authorities.However, the environment and new regulation underthe reform era has given BPK-Rl an oppo4tunity to improve its role. Therefore, BPK tries to develop and implement a new strategy, like assisting Parliament in developing control on the sys-tem of state finance administration to include check and balances mechanism bythe Treasurer, Intemal Auditor and Extemal Auditor, as well as to put back BPK-RI as the only extemal auditor the paper discusses normatively the way to optimize the role of BPK.Keywords: Public audit, public finance, public organization, BPK